แนวทางการพัฒนาประสิทธิภาพการให้บริการประชาชนของข้าราชการศาลยุติธรรม จังหวัดสุราษฎร์ธานี - รัตนมา ไพรวัลย์ (Academic Journal Phranakhon Rajabhat University, 2017)
The purposes of this research were to study: 1) the factors affecting the efficiency of the services of the government officers of the Court of Justice in SuratThani 2) such factors as compared factors compared to personal characteristics affecting the efficiency of the services, and 3) the problems and suggestions for the improvement of services. Research and development methodology conducted through mixed methodology of quantitative and qualitative research. Conducted by the main qualitative research methodology, key informants was the 1,500 visitors of the Court of Justice in SuratThani. The research instruments were questionnaires (0.85 reliability) with open-ended questions and close-ended questions, and focus group discussion. Data was analyzed by content analysis. By quantitative research, sample size was 300 which was selected based on nonprobability sampling method. The research instruments were questionnaires with open-ended questions andclose-ended questions. The data were analyzed by using SPSS computer software for descriptive statistics. The statistics used in data analysis were basic statistics for analysis mean score, percentage and standard deviation, and the testing fools were t-test and one-way ANOVA. The results were as follows: 1. The overall factors affecting the efficiency of the services were rated high and highest. When considering each aspect, the staff was rated highest; the licit followed; the sufficiency and promptness were rated high .The aspect which received the lowest score was the promptness. 2. The comparison of the factors and the participants personal characteristics found 0.05 statistical significance. 3. Means of development were establishing a map, session times, advising staff, well-written forms , and one-stop service spots for efficient services.